Analysis of the Application of Blockchain Technology in Learning Evaluation Systems in Higher Education - Adelio Darel Chatra (Journal of Education Innovation and Curriculum Development, 2024)
This research explores the application of blockchain technology in learning evaluation systems within higher education, focusing on its potential to address issues such as data security, transparency, and trust in academic records. Blockchain offers a decentralized, tamper-proof platform for managing academic data, which can help mitigate challenges like fraud, cheating, and difficulty in tracking student progress. The study reviews existing literature on the use of blockchain in education, particularly in grading, credentialing, and the management of academic achievements. It also identifies the technical, operational, and institutional challenges involved in implementing blockchain, including high implementation costs, resistance to change, lack of expertise, and regulatory issues. The findings suggest that while blockchain presents significant advantages, including enhanced data security and improved trust among stakeholders, its adoption faces substantial barriers. These challenges require collaborative efforts from educational institutions, policymakers, and technology providers to overcome. Overall, the research concludes that blockchain has the potential to revolutionize learning evaluation systems, offering a more secure, efficient, and transparent approach to academic assessment and credentialing in higher education.